2017
DOI: 10.1093/jmammal/gyw145
|View full text |Cite|
|
Sign up to set email alerts
|

Gray wolf mortality patterns in Wisconsin from 1979 to 2012

Abstract: Starting in the 1970s, many populations of large-bodied mammalian carnivores began to recover from centuries of human-caused eradication and habitat destruction. The recovery of several such populations has since slowed or reversed due to mortality caused by humans. Illegal killing (poaching) is a primary cause of death in many carnivore populations. Law enforcement agencies face difficulties in preventing poaching and scientists face challenges in measuring it. Both challenges are exacerbated when evidence is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
98
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 36 publications
(103 citation statements)
references
References 44 publications
5
98
0
Order By: Relevance
“…The former had few roads, and few people, whereas the latter had more of both suggesting that the relative risk from humans for marked and unmarked animals might be influenced by whether humans can detect collars and are killing wolves legally. A study in Wisconsin, across a landscape with denser human activity including many roads, people, livestock, hunters, hounds, etc., produced an estimated 28% higher mortality rate for unmarked gray wolves than for marked wolves when illegal killing comprised almost half of all deaths ( Treves et al 2017b ). Despite current uncertainty about why marked or unmarked wolves face different rates of mortality from humans in different systems, all these studies converge to suggest that the traditional assumption is unsupported: fates of marked wolves do not seem to accurately represent the risk and rates of mortality for the broader population.…”
mentioning
confidence: 99%
“…The former had few roads, and few people, whereas the latter had more of both suggesting that the relative risk from humans for marked and unmarked animals might be influenced by whether humans can detect collars and are killing wolves legally. A study in Wisconsin, across a landscape with denser human activity including many roads, people, livestock, hunters, hounds, etc., produced an estimated 28% higher mortality rate for unmarked gray wolves than for marked wolves when illegal killing comprised almost half of all deaths ( Treves et al 2017b ). Despite current uncertainty about why marked or unmarked wolves face different rates of mortality from humans in different systems, all these studies converge to suggest that the traditional assumption is unsupported: fates of marked wolves do not seem to accurately represent the risk and rates of mortality for the broader population.…”
mentioning
confidence: 99%
“…Systematic errors in attributing poaching to Wisconsin wolf carcasses ranged from 6–37% depending on which subsample one examined, as reported by veterinary pathologists contributing to Treves et al . [ 13 ]. Both Olson et al .…”
mentioning
confidence: 99%
“…[ 10 ] and Treves et al . [ 11 , 13 ] agree that a high proportion of radio-collared wolves disappeared without trace (unknown fate), which must be addressed in some way in any analysis of poaching [ 11 ]. Most importantly, Olson et al .…”
mentioning
confidence: 99%
“…Instrumented versus non-instrumented individuals have been suggested to have different survival rates in other large carnivore populations (Schmidt et al 2015, Borg et al 2016, Treves et al 2017, but evaluating the representativeness of instrumented individuals is particularly challenging as it also requires to obtain data on non-instrumented individuals. Using a comprehensive spatially explicit population-level model taking into account imperfect detection inherent to non-invasive genetic sampling, we showed that GPS collared large carnivores may not always constitute a representative sample of the population for the estimation of survival rates.…”
Section: Discussionmentioning
confidence: 99%